ECB Monetary Policy in a Quandary - Kerstin Bernoth; Marcel Fratzscher (Wirtschaftsdienst)
Abstract It seems clear that the ECB will raise interest rates in July 2022 and end its asset purchase program. This should send a strong and important signal to markets and economic players that the ECB continues to take its mandate for price stability seriously. However, it cannot be said with absolute certainty that these monetary policy decisions herald the start of a gradual tighter stance toward monetary policy normalisation. This is because economic uncertainty is currently extremely high. The ECB therefore finds itself in a difficult dilemma: It must take decisive action against high inflation, but should retain plenty of flexibility to be able to respond to a renewed crisis.